Water balance computation and water quality improvement evaluation for Yanghe Basin in a semiarid area of North China using coupled MIKE SHE/MIKE 11 modeling. Issue 1 (5th July 2021) - Liu, Ruifen; Li, Zeshi; Xin, Xiaokang; Liu, Defu; Zhang, Jialei; Yang, Zhengjian
Abstract: Water shortage and water pollution are two prominent issues in North China. Understanding hydrological cycle and water quality changes in response to pollution control measures is fundamental for a better water management there. Using coupled MIKE SHE/MIKE 11 modeling, various hydrological components in Yanghe Basin in a semiarid area of North China were quantified for three typical hydrological years and concentrations of COD and TP in a national monitoring section of Yanghe were evaluated with/without pollution control measures. The modeling results show that the underground water storage of Yanghe Basin becomes depleted due to evapotranspiration compensation and groundwater utilization regardless of hydrological condition, indicating an unsustainable in-situ water resource utilization. Water quality goals set for Yanghe (COD ≤ 20 mg/L and TP ≤ 0.2 mg/L) can hardly be achieved if pollution control measures are not taken, especially for a dry hydrological year. Depending on hydrological conditions, non-point source control technology-related projects in a 109-km 2 village and a 7-km river-channel wetland in mainstream of Yanghe will have a positive effect or negligible effect on water quality improvement. To meet water quality goals, implementation of three wetlands is an effective and economic way. HIGHLIGHTS: A coupled MIKE SHE/MIKE 11 model is constructed for Yanghe Basin in North China. Yanghe Basin undergoes unsustainable water resource utilization, with evapotranspiration surpassing rainfall. Demonstration water projects on a small scale have either a positive or negligible effect on water quality of Yanghe. Implementation of three river-channel wetlands is an effective and economic way to achieve water quality goals. Graphical Abstract